Urban Wage Premium in Brazil: new evidence about informality and gender - Almeida, Eloiza Regina Ferreira De [UNIFESP] (2020)
The urban wage premium (UWP) is the positive wage differential in dense geographical areas. Its analysis is heavily founded on the observation that, everything held constant, wages are higher in more populated areas, that is, denser places pay higher salaries. It is quite frequent, to identify the UWP using administrative registers filled by firms, restricting the analysis to male workers (even if women’s data are available) with a formal contract. This is a issue for Brazil because informal workers have non-despicable participation in the workforce. Besides, a reduced number of studies focus on analyzing and identifying female UWP. This dissertation proposes to evaluate if and when that groups of workers benefit differently from the agglomeration effects, by including the UWP estimation for informal workers and women, and by focuses on a developing country. We address this investigation by analyzing Brazilian labor market using the Continuous Brazilian National Household Sample Survey (PNADC), a comprehensive longitudinal database that covers the period from 2012 Q1 to 2019 Q3, which allows the analysis of the heterogeneity of the formality status and many other intra-group characteristics, including gender. Chapter 2 focus on male UWP and its contribution rely on closing some literature gaps and enriching the UWP assessment. The results show that previous UWP studies underestimate the UWP for the whole labor market since formal workers UWP is half of the informal ones, and both sectors show a non-homogeneous UWP according to agglomeration levels, with different patterns. An evidence that disregarding these groups of workers hides the complexity inherent of their insertion in the large urban labor markets. In its turn, Chapter 3 contributes to the traditional UWP literature by investigating a neglected group of workers—the women—and concentrating on individual characteristics such as the position at the household, the marital status, and the presence of children, besides the formality status, for which, to our knowledge, no attempt to female UWP estimation was performed. Additionally, it empirically contributes to UWP literature by estimating and correcting the sample selection bias, related to the participation in the labor market, which is particularly relevant to female workers, and by use quantile regressions to identify whether the magnitude of UWP is different throughout the distribution of wages. Therefore, the main conclusion indicates that the previous UWP results are underestimated, since female workers are neglected. Also, the UWP could be over or underestimated for women and men if the wage distribution is disregarded. We find strong evidence that the agglomeration effects do not benefits the workers equally and a higher female UWP can also be attributable to the changes in female labor market composition. Denser areas tend to be more favorable to women and informal workers.